ANALISIS DATA PANEL TRANSMISI HARGA BERAS DI PROVINSI LAMPUNG - Riri Wulandari; Novi Rosanti; Lina Marlina (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2024)
The aims of this research are to examine  the transmission of rice prices  from the producer (miller) level to the consumer vertically, and to analyze  the factors that influence  determination of rice princes  at the producer (miller) level in Lampung Province. The type of method applied in this research was  descriptive research with  quantitative approach. Data analysis was carried out using panel data from January 2020 to December 2022 fron  15 regencies/cities in Lampung Province.  In addition, the data in this research was  also  analyzed by using  Asymmetric Error Correction Model (AECM) and Ordinary Least Squares (OLS). The results obtained in this research indicate that  a symmetrical transmission pattern of rice prices in the short term and an asymmetrical transmission pattern in the long term are occured in Lampung Province. Factors that influence the price of rice at the producer (miller) level in Lampung Province are the consumer price of rice, the price of imported rice, rice consumption, and the producer price of corn.Key words: economic valuation, travel cost method, visitor satisfaction